How Does the Multiple Intelligence Knowledge Influence English as a Second Language (ESL) Instructor's Teaching Strategies? - Iziana Hani Ismail; Nur Anneliza Abd Latip; Wardatul Akmam Din; Suyansah Swanto (Global Academic Excellence, 2022)
The purpose of this study is to identify the level of Multiple Intelligence knowledge among the English language instructors in Sabah. 32 respondents from four educational institutions in Kota Kinabalu participated in this research. The data was obtained through a set of questionnaires that was modified and adapted from Thomas Armstrong (1994) to suit the objectives of this research. The modification and adaptation of the research instruments was done to meet the research objectives and the situation of the research. The set of questionnaire comprises of three parts. Part A touches on the demographic characteristics of the English language instructors, part B focuses on the knowledge level of the theory, and Part C targets on the teaching strategies in the English language classrooms. The marks were counted manually to find the connection between the knowledge level of Multiple Intelligences and the teaching strategies of the instructors in the classrooms. The finding of this research indicates that the English language teachers with excellent level of Multiple Intelligence knowledge do not necessarily have excellent varieties of teaching strategies, and vice versa.